Effects of perinatal exposure to bisphenol A on the intraprostatic levels of aromatase and 5α-reductase isozymes in juvenile rats. (May 2018) - Castro, Beatriz; Sánchez, Pilar; Torres, Jesús M.; Ortega, Esperanza
Abstract: The impact of bisphenol A (BPA) on the prostate gland has taken center stage, with a special focus placed on understanding how BPA affects prostate physiopathology. In this study, we evaluated the ability of lower doses of BPA to induce alterations in 5α-R isozymes and aromatase, in the prostate of juvenile rats exposed during developmental stage. Gestating Wistar rats were treated s.c with either vehicle or BPA (2.4 and 10 μg/kg b.w./day) from gestational day 12 to parturition. Then, male pups were s.c treated from postnatal day 1 through day 21, when they were euthanized and qRT-PCR, western blot and hormone levels determination were performed. We found that BPA at dose of 2.4 and 10 μg/kg b.w./day significantly decreased the mRNA and protein levels of 5α-R2. However, neither 5α-R1 nor 5α-R3 was affected by this exposure. BPA at dose of 10 μg/kg b.w./day significantly increased the mRNA and protein levels of aromatase. BPA also decreased plasma levels of both testosterone and dihydrotestosterone and increased estradiol. These data lend support that low-dose BPA during fetal and neonatal prostate development interfere with in situ estrogen and androgen production in the prostate gland of juvenile rats through the enzymes aromatase and 5α-Reductase. Graphical abstract: Highlights: Low-doses of BPA considered safe for humans were administered during the developmental stage of rat. Low doses of BPA administered during developmental period decreased the intraprostatic expression of 5α-R2. Low-doses of BPA administered during developmental period increased the intraprostatic expression of aromatase. Low-doses of BPA administered during developmental period modified plasmatic levels of androgens and estrogens. Low-doses of BPA administered during developmental period may be harmful for the prostate.